Stereo olfaction underlies stable coding of head direction in blind mice - Kadjita Asumbisa; Adrien Peyrache; Stuart Trenholm (Nature Communications)
Abstract Stereo olfaction, the difference in odor concentration between the two nostrils, has been shown to affect a variety of animal behaviors, including olfactory search. However, it is unknown whether stereo olfaction can enable the formation of allocentric spatial representations. Here, recording from head direction (HD) cells in the anterior dorsal nucleus of the thalamus in blind mice—a model system for studying olfaction-dependent allocentric spatial representations—we find that inhibiting stereo olfaction, by blocking olfactory processing in one nostril or merging the airflow going to both nostrils, drastically impairs head direction coding. To assess the behavioral impact of impaired HD cell tuning caused by loss of stereo olfaction, we developed a closed-loop head direction preference assay, in which a mouse received medial forebrain bundle reward stimulation upon orientating its head in a specific direction. We find that inhibiting stereo olfaction significantly impairs performance in the HD preference assay. These results reveal that stereo olfaction is required for mice to use smell to form a stable allocentric spatial representation of head direction.